The Use of Code Mixing by Indonesian Youtubers Living in Germany - Nessa Aqila Anggraini (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This article analyzed code mixing which occurred in two videos from Gita Savitri and Sarrah Nurul youtube channels. They both are Indonesian students who are living in Germany. The aims of this research are to find out the types of their code mixing and the reasons why they mixed their code while they were talking in their videos. The data were taken from utterance of Gita and Nurul in their videos were uttered in Indonesian and mixed by English utterance. The writer conducted the analyses types of code mixing based upon classification by Pieter Musyken (2000) and conducted analyses of reasons based upon Hoffman (1991). Through the analyses there are 3 types code mixing were occurred (1) insertions, (2) congruent lexicalizations and (3) alternations. There were 6 reasons doing code mixing found through this research, they are (1) clarifying the speech content (2) talking about a particular topic (3) quoting (4) repetition for clarification (5) showing empathy (6) to express group identity.